Dry sliding wear behaviour of nickel-, iron- and cobalt-based superalloys. (1st September 2013) - Mishra, S B; Chandra, K; Prakash, S
Abstract : Dry sliding wear behaviour of nickel-, iron- and cobalt-based superalloys has been investigated using pin-on-disc wear test rig. Superni 600 has shown the highest coefficient of friction, whereas that of Superco 605 is found to be least. Superfer 800H has shown the lowest value of specific wear rate whereas Superni 600 has given highest specific wear rate, followed by Superni 75. The worn samples were analysed with SEM, and the wear debris was analysed using XRD and SEM. Nickel based superalloys have shown comparatively higher wear rates than the cobalt and iron based superalloys due to the formation of NiO.